Why do portfolio choice models predict inelastic demand? - Davis, Carter; Kargar, Mahyar; Li, Jiacui (Journal of Financial Economics, 2025)
Classical asset pricing models predict that optimizing investors exhibit extremely high demand elasticities, while empirical estimates are significantly lower—by three orders of magnitude. To reconcile this disparity, we introduce a novel decomposition of investor demand elasticity into two key components: “price pass-through”, which captures how price movements forecast returns, and “unspanned returns”, reflecting a stock’s lack of perfect substitutes. In a factor model framework, we show that unspanned returns become significant when models include “weak factors”. Classical models overestimate demand elasticity by assuming both very low unspanned returns and high price pass-throughs, assumptions that are inconsistent with empirical evidence.